2010
DOI: 10.1111/j.1542-4758.2010.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and monocyte activation in chronic kidney disease patients under hemodialysis and its relationship with resistance to recombinant human erythropoietin and to the hemodialysis procedure

Abstract: The aim of the present work was to further clarify leukocyte activation due to hemodialysis (HD) procedures and to investigate its relationship with recombinant human erythropoietin resistance. Therefore, we studied the expression of CXCR1 and CD11b on neutrophils, as well as the monocyte expression of CD11b, HLA-DR, and CD14. We studied 34 chronic kidney disease (CKD) patients under HD and recombinant human erythropoietin treatment (26 responders and 8 nonresponders to recombinant human erythropoietin therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
3
12
1
1
Order By: Relevance
“…It has been shown that activated antigen-specific T cells, B cells, and monocytes produced BDNF 18. Uremic inflammatory state is characterized by enhanced immune system which involves both T lymphocytes and monocytes 19. Therefore, it is postulated that chronic inflammatory condition and enhanced immune system is associated with the production of BDNF, which may explain the reason that the plasma BDNF level in non-diabetic HD patients was higher compared to that of control subjects in this study.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown that activated antigen-specific T cells, B cells, and monocytes produced BDNF 18. Uremic inflammatory state is characterized by enhanced immune system which involves both T lymphocytes and monocytes 19. Therefore, it is postulated that chronic inflammatory condition and enhanced immune system is associated with the production of BDNF, which may explain the reason that the plasma BDNF level in non-diabetic HD patients was higher compared to that of control subjects in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, although HD activates inflammatory responses, which promote MMPs release [19], no study has shown increased MMP-2 levels after an HD session. Neutrophil and monocyte activation in CKD patients under HD have been reported [37]. It is expected that increasing neutrophil MMP-9 could be detected in the circulation of HD patients under HD.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, darbepoetin alpha treatment was associated with an increase in MIF, which helps to sustain macrophage activation and is an important mediator of anemic complications and bone marrow suppression during malaria infection [31,32], and could therefore also contribute to resistance to EPO. Furthermore, in patients with chronic kidney disease, nonresponders to EPO treatment are characterized by enhanced activation of both monocytes [33] and T cells [34]. Thus, although the RED-HF trial failed to detect a benefit of an erythropoiesis stimulating agent on clinical outcomes, leukocyte activation markers could be potentially identify patients that could have advantage of EPO treatment.…”
Section: Discussionmentioning
confidence: 99%